Students' Perceptions of the Implementation of Learning at the Japan Internship Pusdiklat Batusangkar - Kemala, Nina; Natsir, MHD (SPEKTRUM: Jurnal Pendidikan Luar Sekolah (PLS), 2024)
The background of this research is the high perception of participants at LKP Yuko Tesa Mirai Padang because it is a special Japanese-language education and training center that provides opportunities for people who wish to have the opportunity to work abroad, especially Japan. This study aims to (1) describe the perceptions of the Batusangkar Japanese Intern Training Center participants towards the teaching staff, (2) describe the Batusangkar Japanese Intern Training Center participants' perceptions of the facilities, (3) describe the perceptions of the Batusangkar Japanese Intern Training Center participants towards learning media, (4) describe the participants' perceptions Japanese Intern Training Center Batusangkar on learning materials. This type of research is a descriptive quantitative approach. The population in this study were 28 people. The sampling technique used cluster random sampling of 20 people. Data collection techniques using a questionnaire. The data analysis technique uses the percentage technique to see the perceptions of the students of the Batusangkar Japanese Intern Training Center. The results of the conclusions of this study indicate that the perceptions of students from the Batusangkar Japanese Intern Training Center based on all indicators are categorized as good, this is evidenced by the high percentage in the always category.